LATEST EXHIBITION AT MGTF: 2 SERIES ARTWORK FROM THAILAND - 4 APRIL 2016 – 5 MAY 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 5 April 2016 – Universiti Sains Malaysia (USM) Muzium dan Galeri Tuanku Fauziah (MGTF) is currently hosting an exhibition named 2 Series Artwork from Thailand titled “Space and Time of Serenity” by Manee Meemak and “Colour of Faith and Serenity” by Pongsiri Kiddee from 4 April 2016 to 5 May 2016.